PENGARUH KINERJA LINGKUNGAN, CARBON EMISSION DISCLOSURE, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Fitriana, Desi Amanatul; Wiratno, Adi; Pratiwi, Umi; Ulfah, Permata (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2024)
This study aims to examine the effect of environmental performance, carbon emission disclosure, and financial performance on firm value. The population used in this study are companies in the energy, industrial process and product use (IPPU), agriculture, building, transportation, waste management, and forestry sectors listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The sample of this study was selected using purposive sampling method, namely with 3 predetermined criteria, among others: listed on the SRI-KEHATI Index, participating in KLHK PROPER activities, and mentioning one of the carbon disclosure information in the annual report and sustainability report. The analysis method used in this study is multiple regression analysis techniques using the IBM SPSS 23 program. The multiple linear regression model in this study has an Adjusted R2 value of 24%, which means that the company's value can be explained using environmental performance variables, carbon emission disclosure, and financial performance where the remaining 76% is influenced by other factors. The results of this study indicate that environmental performance has a negative effect on firm value, carbon emission disclosure has a positive effect on firm value, and financial performance has a positive effect on firm value.